D/H in the refractory organics of comet 67P/Churyumov-Gerasimenko measured by Rosetta/COSIMA. Issue 4 (17th April 2021) - Paquette, J A; Fray, N; Bardyn, A; Engrand, C; Alexander, C M O'D; Siljeström, S; Cottin, H; Merouane, S; Isnard, R; Stenzel, O J; Fischer, H; Rynö, J; et al.
ABSTRACT: The D/H ratio is a clue to the origin and evolution of hydrogen-bearing chemical species in Solar system materials. D/H has been observed in the coma of many comets, but most such measurements have been for gaseous water. We present the first in situ measurements of the D/H ratios in the organic refractory component of cometary dust particles collected at very low impact speeds in the coma of comet 67P/Churyumov-Gerasimenko (hereafter 67P) by the COSIMA instrument onboard Rosetta . The values measured by COSIMA are spatial averages over an approximately 35 × 50 µm 2 area. The average D/H ratio for the 25 measured particles is (1.57 ± 0.54) × 10 −3, about an order of magnitude higher than the Vienna Standard Mean Ocean Water (VSMOW), but more than an order of magnitude lower than the values measured in gas-phase organics in solar-like protostellar regions and hot cores. This relatively high averaged value suggests that refractory carbonaceous matter in comet 67P is less processed than the most primitive insoluble organic matter (IOM) in meteorites, which has a D/H ratio in the range of about 1 to 7 × 10 −4 . The cometary particles measured in situ also have a higher H/C ratio than the IOM. We deduce that the measured D/H in cometary refractory organics is an inheritance from the presolar molecular cloud from which the Solar system formed. The high D/H ratios observed in the cometary particles challenges models in which high D/H ratios result solely from processes that operated in the protosolar disc.